Identification Of Diseases On Coffee Plant In Cangkringan, Sleman, Yogyakarta - Yohanes Yolland Aliandu; Achmad Himawan; Elisabeth i Nanik Kristalisas (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Many different kinds of plants, including coffee plants, are susceptible to disease. In Cangkringan, Sleman, Yogyakarta, this study aims to discover diseases. Compute the percentage of disease attacks, and determine the causes of diseases that affect coffee plants. The Central Laboratory of the Yogyakarta Institute campus is located in the Sleman Regency's Maguwoharjo District. The sample took place in the hamlets of Kopeng, Petung, and Gondang Pusung in the Cangkringan District, D.I. Yogyakarta. The research was done between March and September of 2021. The survey, collection, and identification of fungi that cause coffee plant illnesses in the field and laboratory were the research techniques used. Additionally, farmers who work on coffee plantations were interviewed. Descriptive analysis was done on observational data related to illness symptoms. According to data on environmental conditions in the three coffee plantations, Petung Hamlet had the highest elevation (875.7 masl), Kopeng Hamlet and Gondang Pusung Hamlet had the highest air temperature (27.9 °C), Gondang Pusung Hamlet had the highest air humidity (75%), Kopeng Hamlet had the highest irradiation intensity (1947 Lux), and the three hamlets' soil pH ranged from 5.5-7. A quantitative analysis of the illness attack rate was performed. On the macro- and micro-morphological characteristics of mushrooms, qualitative analysis was conducted. The findings revealed that fungi were to blame for four different types of coffee plant illnesses. These illnesses include sooty mildew, leaf spot, scurvy, and leaf rust (all caused by the fungus H. vastatrix) (Capnodium sp.). Kopeng Hamlet had the highest incidence of disease attacks, including 9.7% for leaf rust, 11.8% for leaf spots, 4.8% for black fungus, and 2.9% for sooty mildew.